Assessing The Suitability Of The Content And Construct Of The End-Of-Semester Exams For English Class VII MTS PUTRA-PUTRI SIMO According To The 2013 Curriculum - Huda, Samsul Huda (MEDIA DIDAKTIKA, 2024)
This study focuses on the analysis of multiple choice test questions that measure critical thinking and tests of procedural knowledge of grammar material for introductory (beginner) English courses. Sample analysis includes:(1) item difficulty, (2) item differentiation, (3) item validity, and (4) item reliability. To measure the difficulty, a comparison formula is used for the number of respondents who answered correctly versus the number of respondents who answered incorrectly. The Pearson product-moment test is used to measure the validity and uniqueness of the item. The Cronbach alpha test is then used to determine the reliability of the test. The results of the difficulty test classify the test items into "easy", "moderate", and "difficult" categories. The results of the differential performance test classify the candidates into the "good" and "excellent" categories. The validity test proves that all test items are valid. The reliability test shows that the planned test is reliable. Therefore, the designed test items do not need to be fixed and can be used to measure critical thinking skills and procedural grammar.